Exploring low polymer content HPMC hydrophilic matrices - Mason, Laura Michelle (2017)
Extended release oral drug delivery (ER) offers many therapeutic benefits. Hydroxypropyl methylcellulose (HPMC) hydrophilic matrices provide a widely-accepted industrial technology to achieve ER. However, there are significant limitations and the mechanism of drug release is complex. One limitation is polymer content. Manufacturers recommend that at least 30% w/w of a high viscosity HPMC should be included in the dosage form, but lower polymer contents are desirable, for example, when (i) a high drug load restricts tablet size or (ii) in-vivo studies show drug release kinetics to be too slow. The widely-held view has been that matrix properties will worsen as polymer content is lowered, and that matrices will fail, or become erratic in their drug release behaviour. This is thought to be due to increased sensitivity to formulation parameters, manufacturing conditions or external dissolution factors, including the fed or fasted state in-vivo. These failures have been attributed to the belief that a lower polymer content will provide a less stable gel layer, in terms of its diffusion barrier properties, its physical strength and resistance to erosion. These principles have scarcely been challenged, even though there is only sparse evidence in the literature to support them. This thesis aims to address this lack of knowledge by providing a series of systematic studies on the behaviour of ‘low polymer’ matrices, those with a polymer content between 5% and 20% w/w of a high viscosity HPMC. Overall, the presented studies have shown that hydrophilic matrices containing less than 30% w/w HPMC can be designed with effective ER control, thus expanding the formulation space for HPMC-based ER medicines. The first experimental chapter (Chapter 3) focused on the formation and structure of the early gel layer with respect to HPMC polymer content. Confocal laser scanning microscopy was used to visualise and compare the emerging gel layer of matrices with different HPMC contents, and was combined with theoretical predictions from percolation theory, one of the few techniques that provides a guide for formulators on the necessary matrix polymer content. The images showed that at polymer contents above the estimated percolation threshold a continuous gel layer was formed within 15 min, whereas matrices with polymer contents below the threshold were characterized by irregular gel layer formation with little evidence of HPMC particle coalescence. The studies provide, for the first time, physical evidence to validate the use of percolation theory in HPMC matrices and they provide support for use of this theory in the development of low polymer content matrices. Chapter 4 examined the drug release sensitivity of low polymer matrices to dissolution factors such as ionic strength and paddle speed. The presence of salts is known to influence HPMC swelling behaviour, and can affect matrix drug release. It was found in USP apparatus II that, as the matrix polymer content was lowered, drug release rate was faster as paddle speed increased from 25 to 150 RPM. In contrast, dissolution sensitivity was found to be independent of sodium chloride (NaCl) concentration, suggesting that the effects of NaCl are polymer, rather than formulation, mediated. This was a rather surprising result, given that salt is known to influence the rate of polymer swelling, a necessary process for gel layer formation and diffusion barrier development. Chapter 5 compared the behaviour of low polymer matrices in the fed and fasted state under simulated in-vivo conditions. The Dynamic Gastric Model, was used to compare drug release from formulations in the presence or absence of food. This work was one of the first published studies where a series of matrix formulations had been evaluated in the DGM. The studies demonstrated that the drug release from formulations with a matrix polymer content below 30% w/w varied according to prandial state, being slower in the presence of food. Formulations containing 30% w/w HPMC did not show a change in drug release rate according to prandial state, beyond a lag in the fed state. The reasons for this are speculated to be due to the deposition of fats on the matrix surface limiting the initial burst in drug release associated with matrices containing lower polymer contents Chapter 6 and 7 examined formulation variables including HPMC particle size and viscosity grade, tabletting excipients and complementary polymers. It showed how judicious formulation selection could reduce the sensitivity of low polymer content matrices to challenging dissolution conditions. A series of numerical rules were developed which could assist in the development of low polymer content matrices in an industrial context. The thesis has identified several key considerations for developing successful low polymer content matrices and should be helpful in guiding the development of medicines that contain lower than the currently recommended levels of HPMC. It corroborates percolation theory and has shown that the percolation threshold is important in influencing matrix sensitivity to dissolution conditions. It should aid the rational design of formulations that have better in-vivo reproducibility and drug release that is less influenced by gastro-intestinal conditions.